Коренева система рослин і характеристики стебел льону-довгунця - Лімонт, А. С.; Лімонт, З. А.; Limont, A.; Limont, Z. (ЦНТУ, 2022)
В статті досліджені характеристики стебел льону-довгунця залежно від маси коріння однієї рослини та її частки в загальній масі рослин. В якості характеристик стебел прийняті висота рослин, маса насіння з однієї рослини, зігнутість стебел, кількість рослин з рівним стеблом (%), вміст деревини в 10-сантиметровому відрізку стебла на відстані від сім’ядольних листочків до 10 см, 10–20 і 20–30 см, а також вихід волокна з технічної частини стебла. На підставі кореляційно-регресійного аналізу експериментальних даних про масу коріння однієї рослини льону-довгунця, а також частку маси коріння в загальній масі рослин і досліджуваних характеристик стебел, які наведені в літературних джерелах, з’ясовано, що зміна висоти рослин, маси насіння з однієї рослини, кількості рослин з рівним стеблом (%) та вмісту деревини в 10-сантиметровому відрізку стебла на відстані до 10 см від сім’ядольних листочків залежно від частки маси коріння в загальній масі рослин описується рівняннями прямолінійної регресії з додатними кутовими коефіцієнтами. Залежно від цієї ж факторіальної ознаки зміна зігнутості стебел описується рівнянням спадної степеневої функції. The aim of the article was to study the characteristics of long flax stalks depending on the mass of roots of one plant and its share in the total mass of plants. The characteristics of the stems are the height of plants, seed weight per plant, curvature of stems, number of plants with flat stems (%), wood content in a 10-centimeter segment of the stem at a distance of cotyledons up to 10 cm, 10-20 and 20 -30 cm, as well as the output of the fiber from the technical part of the stem. The range of variation of the mass of absolutely dry roots of one plant ranged from 89 to 192 mg for arithmetic mean and standard deviation of 138 and 29.3 mg, respectively, and the coefficient of variation of the empirical distribution of root mass of one plant of the analyzed long flax varieties 21.2%. The share of root mass in the total mass of plants ranged from 19.5 to 32.9%. The main statistical indicators of empirical distributions of the found out characteristics of stalks of flax plants have been determined. Based on correlation-regression analysis of experimental data on the mass of roots of one long flax plant and the studied characteristics of stems, which are given in the literature, it was found that the change in plant height, seed weight per plant, number of plants with flat stems (%) , wood content in a 10-cm segment of the stem at a distance of 10 cm from the cotyledons depending on the proportion of root mass in the total mass of plants, stem curvature depending on the weight of seeds from one plant and stem curvature, wood content in a 10-cm stem segment at a distance of 10–20 and 20–30 cm from the cotyledons, the fiber output from the technical part of the stem, depending on the height of the plants, is described by rectilinear regression equations with positive angular coefficients. Change in the number of plants with flat stems (%) depending on the weight of seeds per plant and plant height, as well as the number of plants with flat stems (%) and wood content in a 10-cm section of stem at a distance of 10 cm from cotyledons depending on from the height of plants is described by the equations of rectilinear regression with negative angular coefficients. The change in the curvature of stems depending on the mass of the roots of one plant and the share of this mass in the total mass of plants is described by the equations of decreasing power functions. The change in the number of plants with a flat stem (%) depending on the root mass of one plant is described by the equation of slow-growing hyperbola. The closest correlation between studies was found between stem curvature and root mass of one plant (negative correlation) with a correlation coefficient of minus 0.706, between stem curvature and the share of root mass in total plant mass (negative correlation) with a correlation coefficient of minus 0.713, between the number of plants with a flat stem (%) and the share of root mass in the total mass of plants and the mass of roots of one plant (in both cases a positive correlation) with correlation coefficients of 0.759 and 0.779, respectively. In the studied relationships, the correlation ratios slightly exceeded the values of the correlation coefficients. A less close positive correlation was found between the wood content in a 10 cm section of the stem at a distance of 10 cm from the cotyledons and the share of root mass in the total mass of plants (correlation coefficient 0.444) and between fiber yield from the technical part of the stem and plant height (correlation coefficient 0.327). A negative correlation with a correlation coefficient of minus 0.336 was found between seed weight per plant and plant height. In these studied relationships, the correlation coefficients slightly exceeded the values of the correlation relations of the performance factors by factorial ones. A positive correlation with a correlation coefficient of 0.114 with a correlation ratio of 0.141 was found between the mass of seeds from one plant and the share of root mass in the total mass of plants. In the rest of the correlations studied, the correlation coefficients ranged from 0.013 to 0.102 and were even smaller. The results of the research can be used in designing the technological process of growing flax, choosing tools for basic tillage and elaboration of technological and operational regulations for the use of mechanization in the preparation and harvesting of Roshen flaxseed.
Root System of Plants and Characteristics of Stalks of Flax
Keywords: льон-довгунець; рослина; коріння; надземна частина; стебло; маса; характеристики стебла; зв’язок; flax; plant; roots; aboveground part; stem; mass; characteristics of stems; connection